Power line harmonic radiation observed by the DEMETER spacecraft at 50/60 Hz and low harmonics. Issue 10 (20th October 2015) - Němec, F.; Parrot, M.; Santolík, O.
Abstract: We present a low‐altitude satellite survey of Power Line Harmonic Radiation (PLHR), i.e., electromagnetic waves radiated by electric power systems on the ground. We focus on frequencies corresponding to the first few harmonics of the base power system frequencies (50 Hz or 60 Hz, depending on the region). It is shown that the intensities of electromagnetic waves detected at these frequencies at an altitude of about 700 km are significantly enhanced above industrialized areas. The frequencies at which the wave intensities are increased are in excellent agreement with base power system frequencies just below the satellite location. We also investigate a possible presence of the weekend effect, i.e., if the situation is different during the weekends when the power consumption is lower than during the weekdays. Such an effect might be possibly present in the European region, but it is very weak. PLHR effects are less often detected in the summer, as the ionospheric absorption increases, and also, the radiation is obscured by lightning generated emissions. This difference is smaller in the U.S. region, in agreement with the monthly variations of the power consumption. The analysis of the measured frequency spectra reveals that although intensity increases at low odd harmonics of base power system frequencies are routinely detected, low even harmonics are generally absent. Finally, we verify the relation of PLHR intensities to the geomagnetically induced currents (GICs) proxy. It is shown that the PLHR intensity is increased at the times of higher GIC proxy values during the night. Key Points: PLHR frequencies in excellent agreement with base power system frequencies Intensity increases at low odd harmonics are routinely detected, and low even harmonics are generally absent PLHR intensity increases at the times of higher GIC proxy values during the night